The Importance of Examining Congenital Hypothyroidism in Connection with Congenital Heart Disease: Letter to Editor - Forod Salehi; Atefe Ziaee; Arvin Mirshahi (Mashhad University of Medical Sciences, 2019)
Dear Editor-in-Chief: I read and enjoyed your stylish article, "Frequency of Congenital Cardiac Malformations in Neonates with Congenital Hypothyroidism", in relation to heart disease with hypothyroidism. As we know, one of the most commonly associated congenital hypothyroidism disorders is congenital heart disease, which has a significant effect on the recovery of patients suffering from these disorders. On the other hand, both of these cases are visible and consistent in patients with Down syndrome. Down syndrome is the most common chromosomal abnormality among live-born infants, which usually has certain characteristic signs, including a variety of dysmorphic features, such as flat facial features, small head and ears, short neck, and congenital malformations, the most important of which are congenital heart diseases and other health problems and medical conditions. In what follows, we will study the diagnosis and treatment of an infant with Down syndrome undergoing surgery due to congenital heart disease, whose late detection of hypothyroidism led to lack of proper response to heart failure correction.